M/G/1/K system with push-out scheme under vacation policy. (1996) - Kasahara, Shoji; Takagi, Hideaki; Takahashi, Yutaka; Hasegawa, Toshiharu
Abstract : We consider an M / G / 1 / K system with push-out scheme and multiple vacations. This model is particularly important in situations where it is essential to provide short waiting times to messages which are selected for service. We analyze the behavior of two types of messages: one that succeeds in transmission and the other that fails. We derive the Laplace-Stieltjes transform of the waiting time distribution for the message which is eventually served. Finally, we show some numerical results including the comparisons between the push-out and the ordinary blocking models.